2017
DOI: 10.1016/j.oceaneng.2017.06.057
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion fatigue crack growth modelling for subsea pipeline steels

Abstract: This work is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International licence Newcastle University ePrints-eprint.ncl.ac.uk Cheng A, Chen NZ. Corrosion fatigue crack growth modelling for subsea pipeline steels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…, k, the covariant of the PCA transformed training input variables-x (np) and θ k , which is independent and identically distributed (iid) random vectors of the model parameter. The RF predictor uses unweighted averages over the collector (ĥ) shown in Equation (18) to generalize the prediction by minimizing the loss function and avoiding overfitting via the convergence of Equation (19) [40]:ĥ…”
Section: Pca-random Forest (Rf) Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…, k, the covariant of the PCA transformed training input variables-x (np) and θ k , which is independent and identically distributed (iid) random vectors of the model parameter. The RF predictor uses unweighted averages over the collector (ĥ) shown in Equation (18) to generalize the prediction by minimizing the loss function and avoiding overfitting via the convergence of Equation (19) [40]:ĥ…”
Section: Pca-random Forest (Rf) Algorithmmentioning
confidence: 99%
“…They proposed a non-deterministic artificial intelligence method that estimated the corrosion at different sections of the pipeline. Many other investigations on the use of artificial intelligence in the estimation of the corrosion defect growth of carbon steel materials used for pipelines also abound in the literature [14][15][16][17][18][19][20][21][22][23]. Notable among these studied is the work on the fatigue crack growth where ANN was employed to investigate the corrosion-fatigue crack of a dual phase steel at different stress intensities inconsideration of the martensite content of 32-76% [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corrosion is considered a significant threat which can affect severely the pipeline's integrity. Regarding corrosion effects, several models are used by researchers to study it (Netto 2009;Vanaei et al 2017;Cheng and Chen 2017;Chiodo and Ruggieri 2009;Majid et al 2010Majid et al , 2012Zhou and Huang 2012;Zhu and Leis 2012;Ma et al 2013;Fekete and Varga 2012;Alamilla et al 2013;Abdalla Filho et al 2014;Khelif 2013, 2015) but the power model constitutes one of the most empirical models which is used to describe the corrosion evolution in time such as uniform corrosion, localized corrosion and corrosion fatigue, or even time-dependent for fracture toughness estimation (Romanov 1957;Li and Mahmoodian 2013;Katano et al 2003). Several works applied the power corrosion model as it is considered indispensable for understanding the corrosion behavior (CSA 2007;DNV 2004;Lee and Pyun 2002;Lee 2005).…”
Section: Corrosion Modelmentioning
confidence: 99%
“…While at high pH medium, the hydrogen-based mechanism was dominant. Cheng et al [8] established a two-component model considering anode dissolution and hydrogen embrittlement based on the fracture mechanics theory, and they applied the model for API 5L X65 pipeline steel. The results showed that the model can control the shape of the simulated crack growth curve and the fatigue crack growth (FCG) rate.…”
Section: Introductionmentioning
confidence: 99%